Recovery of Silver from X-ray Washings - Begum, Shakila; Zeb, Pir Aurang; Sharif, Qazi (Biological Sciences - PJSIR, 2008)
This paper presents the enhanced recovery of silver from polymers and gelatin in X-ray washings by treating with activated carbon at different temperatures and optimizing the parameters as temperature, pH and acid base concentrations. It was found that at pilot scale silver recovery increased through treatment with activated carbon and in comprison to the temperature of 20 °C, at 50 °C, the recovery increased from 82.57% to 94.04%.